Biomimetic design and integrated biofabrication of an in-vitro three-dimensional multi-scale multilayer cortical model - Ling Wang; Luge Bai; Sen Wang; Jiajia Zhou; Yingjie Liu; Chenrui Zhang; Siqi Yao; Jiankang He; Chaozong Liu; Dichen Li (Materials Today Bio)
The lack of accurate and reliable in vitro brain models hinders the development of brain science and research on brain diseases. Owing to the complex structure of the brain tissue and its highly nonlinear characteristics, the construction of brain-like in vitro tissue models remains one of the most challenging research fields in the construction of living tissues. This study proposes a multi-scale design of a brain-like model with a biomimetic cortical structure, which includes the macroscopic structural features of six layers of different cellular components, as well as micrometer-scale continuous fiber structures running through all layers vertically. To achieve integrated biomanufacturing of such a complex multi-scale brain-like model, a multi-material composite printing/culturing integrated bioprinting platform was developed in-house by integrating cell-laden hydrogel ink direct writing printing and electrohydrodynamic fiber 3D printing technologies. Through integrated bioprinting, multi-scale models with different cellular components and fiber structural parameters were prepared to study the effects of macroscopic and microscopic structural features on the directionality of neural cells, as well as the interaction between glial cells and neurons within the tissue model in a three-dimensional manner. The results revealed that the manufactured in vitro biomimetic cortical model achieved morphological connections between the layers of neurons, reflecting the structure and cellular morphology of the natural cortex. Micrometer-scale (10 μm) cross-layer fibers effectively guided and controlled the extension length and direction of the neurites of surrounding neural cells but had no significant effect on the migration of neurons. In contrast, glial cells significantly promoted the migration of surrounding PC12 cells towards the glial layer but did not contribute to the extension of neurites. This study provides a basis for the design and manufacture of accurate brain-like models for the functionalization of neuronal tissues.